The Indigo Jackal and other stories level 3 - Horsburgh, Nicholas (Karachi : Oxford university press, 2013)
"The Indigo Jackal and Other Stories" (Level 3, Oxford) is a collection of Indian folktales for young readers. The title story follows a jackal who tricks other animals by pretending to be divine after accidentally dyeing his fur blue. The other stories teach lessons about kindness, intelligence, and honesty. Written in simple language, the book introduces young readers to Indian folklore and moral values.
Keywords: English : Short stories; Oxford : Level 3